ANALISIS WACANA KRITIS PADA TEKS BERITA ONLINE TUTUP PT. TOBA PULP LESTARI (TPL) SUMATERA UTARA - Sinurat, Vinnyta Cechylia; Junifer Siregar; Saragih, Vita Riahni; Sirait, Jumaria; Silitonga, Immanuel Doclas Belmondo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the construction of online news discourse on the closure issue of PT. Toba Pulp Lestari (TPL) in North Sumatra as reported by Detik.com and Kompas.com. The research problem focuses on how online media represent social conflict, environmental damage, indigenous communities, corporations, and government roles through news texts. This study aims to describe textual representation, discursive practice, and social practice using Norman Fairclough’s critical discourse analysis model. This research employed a descriptive qualitative method, with data consisting of four online news texts supported by interviews and documentation. The data were analyzed through reduction, display, and conclusion drawing. The results show that indigenous communities are dominantly represented as victims of injustice, land dispossession, and ecological damage, while PT. TPL is represented as a corporation associated with agrarian conflict. Detik.com tends to provide space for contesting statements between civil society, government, and the company, whereas Kompas.com more strongly highlights public pressure, moral voices, and the policy process. The news discourse also constructs a contestation of meaning among society, corporations, and the state.